Morphophysiological indices of internal organs of the dice snake Natrix tessellata (Reptilia, Colubridae) of the Dnieper river in the Steppe - Yermolenko, S.V.; Gagut, A.M.; Gasso, V.Ya. (Збірник праць Зоологічного музею, 2016)
We studied morphophysiological indices of organs of the dice snakes, Natrix tessellata (Laurenti, 1768), from three populations in the Steppe Zone of Ukraine along the Dnieper River. The specimens were collected in 2013–2016 in three areas: Prydniprovska Thermal Power-Station (Dnipro City), the National Nature Park “Velykyi Luh”, Zaporizhia region, and Majorova Balka (the ravine closed to Majorka village, Dnipro district, Dnipropetrovska region). Studied biotopes differ in some abiotic parameters and the level of anthropogenic load. Significant differences in kidneys and liver indices between sexes were noted. The relative mass of lung and heart diverges between animals from different studied sites. Изучены морфофизиологические характеристики органов водяного ужа Natrix tessellata (Laurenti, 1768) из трех популяций, обитающих в условиях степного Приднепровья. Материал собран в период 2013–2016 гг. на территории, прилегающей к Приднепровской ТЭС (г. Днипро), в биотопах Национального природного парка «Великий Луг» (Запорожская обл.) и Майоровой балки (с. Майорка, Днипровский район, Днепропетровская обл.). Исследования проводились в биотопах с разными абиотическими условиями и антропогенной нагрузкой. Выявлены достоверные межполовые отличия индексов почек и печени. Относительный вес легкого и сердца различался у животных из разных мест обитания, в которых проводились исследования. Вивчено морфофізіологічні характеристики органів водяного вужа Natrix tessellata (Laurenti, 1768) з трьох популяцій, що мешкають в умовах степового Придніпров'я. Дослідження проводилися в біотопах з різним рівнем антропогенного навантаження. Матеріал зібраний в період 2013–2016 рр. на території, прилеглій до Придніпровської ТЕС (м. Дніпро), в біотопах Національного природного парку «Великий Луг» (Запорізька обл.) і Майорової балки (с. Майорка, Дніпровський район, Дніпропетровська обл.). Дослідження проводилися в біотопах з різними абіотичними умовами і антропогенним навантаженням. Виявлено достовірні міжстатеві відмінності індексів нирок і печінки. Відносна вага легені і серця відрізнялася у тварин з різних місць проживання, в яких проводилися дослідження.